Teoría política y aculturación en los apologetas griegos de fines del reinado de Marco Aurelio - González Román, Cristóbal (Antigüedad y Cristianismo, 1990)
At the end of the reign of Marcus Aurellius we find in the writings of Meliton of Sardes and of Atenagoras the appearance of precise reflexions on the characteristics of the royalty and on the transmission of the royal power which denotes the existence of a process of helenistic aculturation of Christianity.